Energy-saving H2 production through H2S electrolysis accompanying solid sulfur recovery using a Ni3S2/Ni3N heterostructure as the electrocatalyst - Sinha, Nibedita; Das, Chandni; Pal, Santanu; Roy, Poulomi (ACS Applied Energy Materials, 2025)
The thermodynamically feasible electrochemical sulfion oxidation reaction (SOR) is advantageous for degrading the toxic H2S pollutant into the value-added chemical sulfur but often suffers from catalyst passivation due to blockage of electroactive sites by accumulation of solid sulfur. The strategic design of electrocatalysts with enhanced electrochemical activity and improved sulfur tolerance is thereby crucial to fully harness the benefits of the SOR. In this work, we developed nickel sulfide nanorods decorated with nickel nitride nanoparticles directly grown on conductive nickel foam as an efficient trifunctional electrocatalyst for the SOR, oxygen evolution reaction (OER), and hydrogen evolution reaction (HER). Optimized Ni3S2/Ni3N showed lower electrode potentials of 0.25, 1.487, and 0.89 V to achieve a benchmark current density of 10 mA cm(-2) for the SOR, OER, and HER, respectively. The hybrid H2S electrolysis setup employing a Ni3S2/Ni3N electrocatalyst drastically reduced the cell potential by 1.24 V compared to that of conventional water electrolysis at a current density of 200 mA cm(-2). Having said that, heterostructure formation not only enhances the activity for the SOR but also helps to avoid sulfur poisoning, enabling the electrocatalyst to sustain for 100 long hours at a high current density of 100 mA cm(-2). Consequently, the approach with the developed electrocatalyst has the ability to reduce the energy consumption by 59.22%, which can make rigorous, economically viable H-2 production driven by solar energy.
Keywords: energy-economic; H-2 production; H2S electrolysis; heterostructure; solidsulfur